2018
DOI: 10.1016/j.jid.2018.06.186
|View full text |Cite|
|
Sign up to set email alerts
|

HSP70iQ435A-Encoding DNA Repigments Vitiligo Lesions in Sinclair Swine

Abstract: Human HSP70i carries a single amino-acid modification within the dendritic cell activating region and tolerizes dendritic cells in vitro. The underlying DNA was used to prevent and treat disease in vitiligo mouse models through reduced dendritic cell activation and diminished skin T-cell infiltration, suggesting the same may be useful for patients. Physiologic differences between mouse and human skin then called for studies in large animals with human-like skin. We established the efficiency of DNA jet injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…This includes evaluating depigmentation, and the persistence of Tregs and melanocytes in the skin. Adoptive transfer of antigenspecific Tregs may offer an exciting opportunity to halt depigmentation and to complement up-and-coming therapeutics such as modified inducible HSP70 to tolerize dendritic cells (DCs) and Janus kinase (JAK) inhibitors to mitigate T cell activation (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…This includes evaluating depigmentation, and the persistence of Tregs and melanocytes in the skin. Adoptive transfer of antigenspecific Tregs may offer an exciting opportunity to halt depigmentation and to complement up-and-coming therapeutics such as modified inducible HSP70 to tolerize dendritic cells (DCs) and Janus kinase (JAK) inhibitors to mitigate T cell activation (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…The same research team then confirmed their initial results in the Sinclair swine model that develops melanomas regressing by immune surveillance, leading to vitiligo-like depigmentation. The findings of this subsequent study showed that treating swine with HSP70iQ435A-encoding DNA induced repigmentation of treated lesions and, most importantly, of distant vitiligo lesions, indicating a possible systemic effect [14]. This approach seems to confer a long-lasting repigmentation.…”
Section: Targeting Innate Immunitymentioning
confidence: 74%
“…A modified version of Hsp70i, Hsp70i Q435A , a reversed depigmentation that was identified in Sinclair Swine recently, has also been observed in mice models, thus providing the rationale for study in human species. Mutant Hsp70i opens a door to potential new treatment for vitiligo patients [39].…”
Section: Innate Immunity Bridges the Gap Between Oxidative Stress Andmentioning
confidence: 99%